2014
DOI: 10.2147/tcrm.s58186
|View full text |Cite
|
Sign up to set email alerts
|

Postural pattern recognition in children with unilateral cerebral palsy

Abstract: BackgroundSeveral different strategies for maintaining upright standing posture in children with cerebral palsy (CP) were observed.PurposeThe purpose of the present study was to define two different postural patterns in children with unilateral CP, using moiré topography (MT) parameters. Additionally, another focus of this article was to outline some implications for managing physiotherapy in children with hemiplegia.Patients and methodsThe study included 45 outpatients with unilateral CP. MT examinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…For this reason, the adoption of a different biomechanical alignment, such as the antepulsion posture, and the use of hip strategy, which needs less effort than the ankle strategy used by children with TD, compensate for the abnormal capacity of children with CP to stay in static position [16][17][18][19] . However, such adaptations demand a considerable effort of posterior antigravity muscles to avoid the fall 20 , which can lead to an overload on the posterior muscular chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the adoption of a different biomechanical alignment, such as the antepulsion posture, and the use of hip strategy, which needs less effort than the ankle strategy used by children with TD, compensate for the abnormal capacity of children with CP to stay in static position [16][17][18][19] . However, such adaptations demand a considerable effort of posterior antigravity muscles to avoid the fall 20 , which can lead to an overload on the posterior muscular chain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 16,17,20 point out that hemiplegia, characterized by motor impairment and unilateral spasticity in the contralateral upper and lower limb to the affected brain hemisphere, leads the child to use the normal halfbody, hindering the weight transfer on the side affected. Diplegic children, on the other hand, with bilateral spasticity, predominant in the lower limbs, present greater difficulties in posture control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…With limited movement in the lower body, the baby is deprived of opportunities to stimulate the motor development of the lower limbs, and later, also rotational movements, which interferes with the totality of ideomotor processes. Despite good treatment outcomes, the support functions of the lower limbs should be carefully monitored using objective measuring tools during the child’s later development to identify any persistent ideomotor abnormalities 19. In later development, children with a history of developmental dysplasia of the hip should also be carefully monitored with regard to the biomechanical functions of the spinal column 20.…”
Section: Discussionmentioning
confidence: 99%
“…However, postural deficit in CP, which involves tone and abnormal reflex activity, increasing of co-contraction of agonists and antagonists, decrease of trunk muscle activation and incoordination, may affect the ability to maintain standing posture and, consequently, the symmetry in the distribution of weight in the sole of the feet. (6,7) Recent studies have shown that children with hemiparetic CP may or may not burden the lower limb affected in bipedalism and that the changes in body posture are also related to this behavior. (5)(6)(7) Regarding to these aspects, the objective of this study was to investigate the distribution of plantar pressures and body posture of children with spastic CP treated at the Pediatric Neurofunctional Ambulatory Rehabilitation Sector of the Physiotherapy Service of the University Hospital of the Federal University of Santa Maria.…”
Section: Introductionmentioning
confidence: 99%